2014
DOI: 10.1177/1545968314545174
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Kinematic Characterization of Reaching Impairments in Mice After a Stroke

Abstract: These results support the use of kinematic analysis in mice as a tool for both detection of poststroke functional impairments and tracking of motor improvements following rehabilitation. Similar studies could be performed in parallel with human studies to exploit the translational value of this skilled reaching analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(85 citation statements)
references
References 31 publications
(81 reference statements)
6
78
0
Order By: Relevance
“…2d–f). Slower, more-variable and more-extraneous movements are observed in the paretic forelimb of rodents after motor system damage than in intact animals 65,67,68 . To reach for food rewards with the paretic forelimb, rodents use compensatory rotational movements of the trunk to extend and control paw position, and use compensatory trunk and head movements to bring the mouth to the paw 16,63,69 .…”
Section: Compensatory Movement Strategiesmentioning
confidence: 93%
See 2 more Smart Citations
“…2d–f). Slower, more-variable and more-extraneous movements are observed in the paretic forelimb of rodents after motor system damage than in intact animals 65,67,68 . To reach for food rewards with the paretic forelimb, rodents use compensatory rotational movements of the trunk to extend and control paw position, and use compensatory trunk and head movements to bring the mouth to the paw 16,63,69 .…”
Section: Compensatory Movement Strategiesmentioning
confidence: 93%
“…Several studies in rodent models of stroke have found that a few weeks of daily training of the paretic forelimb in skilled reaching tasks can improve performance (as measured by the successful retrieval of food rewards), even when abnormalities in the paretic limb movements that are used to perform the task persist, suggesting that the improvements result from compensatory strategies 68,69,93,94 . In rats with substantial motor cortical infarcts, the performance improvements were greatly diminished if the non-paretic forelimb was kept in a sling during daily training, indicating that assistive movements of this limb probably contributed to the improvements 16 .…”
Section: Learning To Compensatementioning
confidence: 99%
See 1 more Smart Citation
“…However, assays for mice need to be developed independently from those utilized in rats since neither training nor performance patterns necessarily overlap between the species. Existing tests meeting these criteria such as skilled pellet retrieval reaching tasks 3-5 can be time consuming to train and score, especially in a manner producing continuous quantification. When behavior is automatically measured rather than scored visually, it can be more easily quantified to a finer degree than is practical with visual scoring.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we describe this assay, which requires the coordination of several forearm muscles. Like existing skilled reach tasks, this assay requires a mouse to reach through a slit to grasp an object in a manner amenable to automated or hand-scored motion analysis 3 , however unlike existing tests the subsequent force exertion on the object is highly constrained and isometric. The task precludes behavioral compensation, shows lasting deficits as a result of photothrombotic cortical stroke, allows for flexibility in different aspects of behavioral measurement, can be trained in a partially automated fashion without close attention, and can be consistently applied in large numbers of mice with efficiency and precision.…”
Section: Introductionmentioning
confidence: 99%